Bikameral Semu dalam UUD 1945: Implikasi terhadap Struktur Fungsi dan Kewenangan MPR Pasca Amandemen - Abdullah Ahmad Hasyim; Isharyanto Isharyanto (Res Publica: Jurnal Hukum Kebijakan Publik, 2026)
The amendments to the 1945 Constitution of the Republic of Indonesia not only restructured the distribution of state power but also reconstructed the national representation system into a pseudo-bicameral model. This model convenes the House of Representatives (DPR) and the Regional Representative Council (DPD) within a single forum, namely the People's Consultative Assembly (MPR), characterized by an asymmetrical distribution of authority. Theoretically, this institutional design presents significant challenges within the framework of representative constitutionalism and deliberative democracy, particularly concerning the quality of territorial representation and the scope of constitutional deliberation. This study aims to analyze the construction of the DPR-DPD relationship within the pseudo-bicameral system and its implications for the deliberative function, the appointment to constitutional offices, and constitutional amendments. Employing a normative legal research methodology, this study utilizes statute, conceptual, and historical approaches. The findings reveal that the dominance of the DPR and the constrained authority of the DPD have resulted in the reduction of the MPR's deliberative function and the erosion of the equilibrium among representative elements. This asymmetric structure generates a tension between the principle of constitutional supremacy and the imperative for inclusive democratic legitimacy. Consequently, strengthening the role of the DPD through a limited constitutional amendment or the reconstruction of the MPR's internal mechanisms constitutes a normative prerequisite for establishing a more deliberative and constitutionally robust representation system.